ASSESSING KNOWLEDGE ABOUT MOTHER-TO-CHILD TRANSMISSION OF HIV/AIDS AMONG MARRIED WOMEN IN INDONESIA - Desy Nuri Fajarningtiyas; Sari Kistiana (JURNAL KESEHATAN REPRODUKSI, 2024)
Assessing Knowledge about Mother-to-Child Transmission of HIV/AIDS Among Married Women in Indonesia Background: The transmission of HIV/AIDS will affect not only women but also their families, including their children’s health and future. Given the quite high rates of vertical transmission as well as early infant transmission, understanding mother-to-child transmission (MTCT) of HIV/AIDS is important for women. Objective: This study aims to examine knowledge about the MTCT of HIV/AIDS among married women and the contributing factors. Method: A weighted sample of 35,479 married women aged 15-49 was drawn from the 2017 Indonesia Demographic and Health Survey. Binary logistic regression for complex sample design was used to examine the associated factors of HIV/AIDS MTCT. Result: Overall, only 58.6% of women had good knowledge of HIV/AIDS MTCT. Women with a comprehensive knowledge of HIV/AIDS (OR: 7.27, 95% CI:6.75-7.83), aged ≥ 35 years (OR:1.33, 95% CI:1.19-1.47), attaining at least secondary education level (OR:1.85, 95% CI:1.71-1.99), having an educated husband (OR: 1.28, 95% CI: 1.11-1.47), coming from richer family (OR:1.41, 95% CI: 1.29-1.54), and residing in urban areas (OR: 1.23, 95% CI:1.13-1.33) tend to have better knowledge of HIV/AIDS MTCT. Conclusion: Enhancing comprehensive knowledge of HIV/AIDS among women and men through both formal and informal education curricula is expected to increase knowledge about MTCT of HIV/AIDS.